Assessment of Maternal and Fetal Outcomes in Preeclampsia: A Tertiary Care Experience - Ambareen Haaris, Sana Gul, Durre Shawar, Sobia Hamza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Preeclampsia is a disorder of pregnancy of hypertension and appears due to high blood pressure and proteinuria after 20 weeks of pregnancy. It is still a significant cause of maternal and perinatal morbidity and mortality especially in low- and middle-income countries. Proper management and early recognition can be of importance towards enhancing better maternal and fetal outcomes. Goals: To examine the maternal and fetal outcomes of pregnant women with preeclampsia and to determine the severity and complications of the condition as provided in the setting of a tertiary care center. Study design: A prospective observational study. Place and Duration of Study: The study was conducted at Department of Gynae & Obs, Khyber Teaching Hospital (MTI) Peshawar from January 2022 to December 2022. Methods: A prospective observational study that was carried out in the department of Obstetrics and Gynecology during 12 months and included 100 pregnant women who were diagnosed with preeclampsia at least 20 weeks of pregnancy. Maternal age, parity, gestational age, level of blood pressure, complications, and fetal outcomes were attached. The statistical package was done in SPSS version 25. The percentages were averaged, standard deviation and p-values determined to assess the significance. Results: A hundred patients were recruited and the mean maternal age was 27.6 \178 w in age. Out of them, 60 percent were displaying mild preeclampsia, and 40 percent were in severe preeclampsia. There was preterm delivery in 36 percent of cases in addition to 28 percent with intrauterine growth restriction (IUGR). Maternal complications were eclampsia (6 percent), HELLP (4 percent) and abruptio placentae (3 percent). The neonatal outcomes demonstrated that 42 percent had low birth weight and 30 percent were admitted at the NICU. Significant relationship (p < 0.05) was found between severity of preeclampsia and adverse outcomes. Conclusion: Preeclampsia has drastic effects on the health of the mother and baby particularly, given it is severe. By correct diagnosis and management in a tertiary care hospital, it is possible to minimize complications and improve outcomes. The study claim the significance of regular antenatal care to detect it. The enhancement of referral mechanisms and maximization of delivery decision are important milestones in ensuring reduction of morbidity and mortality related to this condition. Keywords: Preeclampsia, maternal outcome, fetal complications, tertiary care